2001
DOI: 10.1046/j.1365-2540.2001.00836.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of genetic variability in a population of the edible snail, Helix aspersa Müller, undergoing domestication and short-term selection

Abstract: The evolution of genetic variability is studied in six successive generations of a population originating from wild Helix aspersa. During the first three generations (G1 to G3), no artificial selection was applied. During the next three generations (G4 to G6), two lines were reared: a control line (C) and a line (S) selected for increased adult weight. Genetic variability is described by genealogical parameters (inbreeding, number of founders, effective number of founders and ancestors, effective number of rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…For insect species, it has been observed that the adaptation to laboratory conditions frequently favors individuals with faster life cycles, females with high fecundity at the beginning of the reproductive stage, and males that do not necessarily accomplish all parts of the courting sequences /courtship [ 2 - 4 ]. At a molecular level, changes in the genetic variability have also been observed during the adaptation to laboratory conditions [ 5 - 11 ]. Specifically, the reduction of the population effective size in combination with the confinement to finite spaces has high impact on the genetic variability [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For insect species, it has been observed that the adaptation to laboratory conditions frequently favors individuals with faster life cycles, females with high fecundity at the beginning of the reproductive stage, and males that do not necessarily accomplish all parts of the courting sequences /courtship [ 2 - 4 ]. At a molecular level, changes in the genetic variability have also been observed during the adaptation to laboratory conditions [ 5 - 11 ]. Specifically, the reduction of the population effective size in combination with the confinement to finite spaces has high impact on the genetic variability [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Selection is expected to rapidly reduce the genetic variation, which then stabilizes except in small populations where the erosion of variation continues due to genetic drift and inbreeding. However, many hypotheses underlie these models and few studies have been carried out on real populations under selection (Sorensen and Hill, 1982;Meyer and Hill, 1991;Dupont-Nivet et al, 2001). Dupont-Nivet et al (2001) observed a strong decrease of genetic variation in the two first generations of a snail population undergoing selection followed by an equilibrium phase.…”
Section: Introductionmentioning
confidence: 99%
“…However, many hypotheses underlie these models and few studies have been carried out on real populations under selection (Sorensen and Hill, 1982;Meyer and Hill, 1991;Dupont-Nivet et al, 2001). Dupont-Nivet et al (2001) observed a strong decrease of genetic variation in the two first generations of a snail population undergoing selection followed by an equilibrium phase. Meyer and Hill (1991) reported a reduction of genetic variation during 23 generations in a population of mice selected for food intake.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, negative correlations arise across genic fitnesses in part because genotypes in which both loci have low genic fitness are purged by selection; in this case, however, the bias is not observational but actual, as these low-fitness genotypes are selectively removed from the population. In this genetic context, where selection is imposed artificially through breeding, this biasing effect has been contemplated and modeled; it is known as the "Bulmer effect" [68][69][70][71][72][73]. When a desired (artificially selected) trait is determined by several genetic components, one generation of breeding for the desired trait will result in negative associations among the trait's components.…”
mentioning
confidence: 99%